1977
DOI: 10.1149/1.2133557
|View full text |Cite
|
Sign up to set email alerts
|

Device Quality GaAs Grown at Low Temperature by the Halide Process

Abstract: A study of the parameters which must be controlled to enable the vapor growth of GaAs at low temperature (LT.VPE) using the AsC1JGaAs/H2 system has led to routine growth of MESFET layers at 630~ The source temperature was determined from transport efficiency measurements and set in the range 670~176The growth rate dependence on temperatures and the AsCI~ mole fraction were determined. The morphology of the layer was optimized as a function of the AsCh mole ~raction and the misorientation of the substrate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…By reacting TiCl 4 with silane or silicon chlorides at high temperatures, titanium silicide thin films can be grown. 21,[31][32][33] CVD provides possibilities to prepare kinetically stable phases which are difficult to obtain using the other methods. Recently, by employing variations of the fabrication methods mentioned above, preparations of nanosized one-dimensional (1D) silicides of Ti, V, Cr, Mn, Fe, Co, Ni, and Ta have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By reacting TiCl 4 with silane or silicon chlorides at high temperatures, titanium silicide thin films can be grown. 21,[31][32][33] CVD provides possibilities to prepare kinetically stable phases which are difficult to obtain using the other methods. Recently, by employing variations of the fabrication methods mentioned above, preparations of nanosized one-dimensional (1D) silicides of Ti, V, Cr, Mn, Fe, Co, Ni, and Ta have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The last one is chemical vapor deposition (CVD) reactions. By reacting TiCl 4 with silane or silicon chlorides at high temperatures, titanium silicide thin films can be grown. , CVD provides possibilities to prepare kinetically stable phases which are difficult to obtain using the other methods. Recently, by employing variations of the fabrication methods mentioned above, preparations of nanosized one-dimensional (1D) silicides of Ti, V, Cr, Mn, Fe, Co, Ni, and Ta have been reported. ,, For titanium silicides, these include nanowires (NWs) of TiSi and C54-TiSi 2 , nanopins (NPs) of TiSi, nanobats of Ti 5 Si 4 , and nanonets (NNs) of C49-TiSi 2 , as listed in Table . ,,,,, Previously, we have communicated the growth of Ti 5 Si 3 NWs on top of C54-TiSi 2 thin films grown by reacting titanium subhalides TiCl x (g) , generated by passing TiCl 4(g) over Ti (s) at 1173 K, with Si substrates in a CVD process .…”
Section: Introductionmentioning
confidence: 99%
“…However, with the availability of high purity GaAs material in recent years, AsC1jH2/GaAs solid Source method can be considered seriously as an alternative to produce VPE layers. Recent results have indicated that device quality epitaxial layers, grown with solid GaAs source, with background doping in the mid 10 ls cm -3 range and Hall mobility greater than 5500 cm2/V-s at room temperature can be obtained routinely (1,2).…”
mentioning
confidence: 99%